2020
DOI: 10.4103/jmu.jmu_72_19
|View full text |Cite
|
Sign up to set email alerts
|

Utility of ultrasound elastography to differentiate benign from malignant cervical lymph nodes

Abstract: Background: The purpose of this study was to evaluate the usefulness of strain elastography and acoustic radiation force impulse (ARFI) imaging in the differentiation of benign and malignant cervical lymph nodes (LNs). Materials and Methods: In this prospective study, 50 enlarged cervical LNs (33 benign and 17 malignant) were examined by B-mode ultrasound (US), color Doppler, and strain elastography. Elastographic patterns (1–5) were categorized based on distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Interestingly, false-positive results in our study represented 50% of pattern 3 in elastogram, and the same percentage was also documented by Ishibashi et al 24 Moreover, other studies reported that false-positive diagnoses constituted 3.5 to 33% of pattern 3. 17,19,25 These notable findings can classify pattern 3 as border line or suspicious for malignancy, therefore false-positive results could be expected in this pattern with infectious mononucleosis and granulomatous lymphadenitis. 18 Conversely, the present study did not report any falsenegative results.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, false-positive results in our study represented 50% of pattern 3 in elastogram, and the same percentage was also documented by Ishibashi et al 24 Moreover, other studies reported that false-positive diagnoses constituted 3.5 to 33% of pattern 3. 17,19,25 These notable findings can classify pattern 3 as border line or suspicious for malignancy, therefore false-positive results could be expected in this pattern with infectious mononucleosis and granulomatous lymphadenitis. 18 Conversely, the present study did not report any falsenegative results.…”
Section: Discussionmentioning
confidence: 96%
“…As for the sonographic evaluation, borders, echogenicity, the presence of hilum, patterns of vascularization, and S/L ratio were recorded for each lymph node, thus providing a scoring rubric as previously described in the text. This choice was based on reports in the current literature that describe the single feature as not being accurate enough to distinguish benign from malignant lymph nodes, and the scores based on the combined findings provided more accurate diagnoses, as described in the recent literature available for canine species and people [ 7 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical, axillary, and inguinal lymph nodes are easily evaluated by standard USE; and USE has the potential to non-invasively differentiate tuberculous from metastatic lymph nodes because of the latter’s greater stiffness[ 40 , 41 ]. On strain USE a cut-off value of 3.0 (strain ratio) has been suggested for determining if a mass/tissue is benign or malignant[ 42 - 44 ].…”
Section: Imaging Methods In Tuberculosismentioning
confidence: 99%